Balancing rheology, strength, and thermal performance in sustainable self-compacting mortars incorporating recycled concrete block fines and fine wood dust - Chatveera, Burachat; Chintanapakdee, Chatpan; Saingam, Panumas; Pongsopha, Phattharachai; Hussain, Qudeer; Sua-iam, Gritsada (My University, 2026)
The use of waste-derived materials in cementitious systems has been widely explored; however, limited studies have addressed the combined influence of recycled fine aggregates and bio-based additives under a rheology-controlled design framework. This study investigates the rheology-controlled performance of sustainable self-compacting mortars (SCM) incorporating recycled concrete block fines (RCBF) and fine wood dust (FWD) with calcium carbonate as an inert filler. RCBF replaced natural sand at 5–20% by volume, while FWD was added at 1–5% of binder volume to evaluate their combined influence on fresh behavior, mechanical performance, durability, and thermal conductivity. The results show that increasing RCBF and FWD contents increased viscosity and superplasticizer demand, while compressive strength decreased from 49.66 MPa (control) to 28.1 MPa at the highest replacement level. The mix with 5% RCBF and 1% FWD exhibited the best overall balance, maintaining a compressive strength of 45.1 MPa with moderate water absorption (6.27%) and limited sulfate-induced strength loss (∼4.0%). Across all mixtures, however, strength loss under sulfate exposure ranged from 1.9% to 13.1%. With increasing replacement levels, water absorption increased to 8.39% and ultrasonic pulse velocity decreased, indicating a progressive increase in porosity and internal discontinuity. In contrast, thermal conductivity significantly decreased from 2.133 to 1.311 W/m·K, indicating enhanced insulation performance. These results demonstrate that the combined use of RCBF and FWD enables a controlled trade-off between mechanical and durability properties and improved thermal performance, supporting the development of sustainable SCM systems governed by rheological design rather than strength maximization.
Keywords: Bio-based rheology modifier; Fine wood dust; Recycled concrete block fines; Rheology control; Self-compacting mortar; Thermal-insulating mortar